1995
DOI: 10.1007/bf01892744
|View full text |Cite
|
Sign up to set email alerts
|

Permanent or absorbable sutures for Burch colposuspension?

Abstract: There is no consensus in the present literature on the type of suture material to be used for Burch colposuspension. The authors reviewed the available literature and studied the cure rates of the various studies. Seventeen studies which specified the suture material could be analysed. The mean cure rate in those that used permanent sutures was equal (87%) to the studies which used absorbable sutures. It was concluded that both types of suture material have equal success rates and that, on the basis of the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…A review of 17 studies comparing absorbable with permanent suture showed no significant differences in success rates. 85 Further review of the literature shows that suture type varies with no clear consensus other than a preference toward nonabsorbable sutures. 86,87 The patient should be placed in the dorsal lithotomy position with legs in Allen stirrups.…”
Section: Retropubic Urethropexymentioning
confidence: 98%
“…A review of 17 studies comparing absorbable with permanent suture showed no significant differences in success rates. 85 Further review of the literature shows that suture type varies with no clear consensus other than a preference toward nonabsorbable sutures. 86,87 The patient should be placed in the dorsal lithotomy position with legs in Allen stirrups.…”
Section: Retropubic Urethropexymentioning
confidence: 98%
“…In their review on this issue, Smits-Braat reported an equal cure rate of 87% whether absorbable or permanent sutures were preferred. 2 , 16 We used absorbable suture (1-0 polyglactin) in our cases. This was a necessity, because the Hem-o-Lok™ clips cannot grip nonabsorbable sutures like polypropylene due to its slippery property during retraction.…”
Section: Discussionmentioning
confidence: 99%
“…There is no consensus in the current literature regarding the suture material to be used. In their review on the subject, Smits‐Braat reported equal cure rates of around 87% whether absorbable or permanent sutures were used . Traditionally, the proximal sutures are located 2 to 3 cm lateral to the bladder neck, the distal sutures are placed 2 to 3 cm lateral to the proximal third of the urethra (Figure ).…”
Section: Methodsmentioning
confidence: 99%
“…In their review on the subject, Smits-Braat reported equal cure rates of around 87% whether absorbable or permanent sutures were used. 35 Traditionally, the proximal sutures are located 2 to 3 cm lateral to the bladder neck, the distal sutures are placed 2 to 3 cm lateral to the proximal third of the urethra (Figure 7). They should apprehend the full-thickness of the vaginal wall, right under the mucosa.…”
Section: The Traditional Open Burch Colposuspension Proceduresmentioning
confidence: 99%